Equivalence of outcomes for rural and metropolitan patients with metastatic colorectal cancer in South Australia. Issue 8 (20th October 2014) - Hocking, Christopher; Broadbridge, Vy Tuong; Karapetis, Christos; Beeke, Carol; Padbury, Robert; Maddern, Guy J; Roder, David M; Price, Timothy J
Abstract: Objective: To compare the management and outcome of rural and metropolitan patients with metastatic colorectal cancer (mCRC) in South Australia. Design, setting and patients : Retrospective cohort study of patients with mCRC submitted to the South Australian mCRC registry between 2 February 2006 and a cut‐off date of 28 May 2012. Main outcome measures: Differences in oncological and surgical management and overall survival (calculated using the Kaplan–Meier method) between city and rural patients. Results: Of 2289 patients, 624 (27.3%) were rural. There was a higher proportion of male patients in the rural cohort, but other patient characteristics did not significantly differ between the cohorts. Equivalent rates of chemotherapy administration between city and rural patients were observed across each line of treatment (first line: 56.0% v 58.3%, P  = 0.32; second line: 23.3% v 22.5%, P  = 0.78; and third line: 10.1% v 9.3%, P  = 0.69). A higher proportion of city patients received combination chemotherapy in the first‐line setting (67.4% v 59.9%; P  = 0.01). When an oxaliplatin combination was prescribed, oral capecitabine was used more frequently in rural patients (22.9% v 8.4%; P  < 0.001). No significant difference was seen in rates of hepatic resection or other non‐chemotherapy treatments between cohorts. Median overall survival was equivalent between city and rural patients (14.6 v 14.9 months, P  = 0.18). Conclusion: Patterns of chemotherapy and surgical management of rural patients with mCRC in SA are equivalent to their metropolitan counterparts and lead to comparable overall survival. The centralised model of oncological care in SA may ensure rural patients gain access to optimal care.